Yield and phytochemical characterization of essential oil from Ocimum selloi B. obtained by hydrodistillation and supercritical fluid extraction - Aparecida Salgado de Morais, L.; Ming, Lin Chau [UNESP]; Ortiz Mayo Marques, M.; Almeida Meireles, M. Â (My University, 2011)
The yield and chemical composition of essential oils from leaves of Ocimum selloi B. submitted to organic and mineral fertilization, obtained by hydrodistillation and supercritical fluid extraction (SFE) were compared. Essential oil was extracted in a Clevenger-type apparatus for 2 h 30 min and analyzed by GC-MS (Shimadzu, QP 5050-DB-5 capillary column - 30 m × 0.25 mm × 0.25 μm). Carrier gas was helium (1.7 ml/min); split ratio: 1:30. Temperature program: 50°C, rising to 180°C at 5°C/min, 180°C, rising to 280°C at 10°C/min. Injector temperature: 240°C and detector temperature: 230°C. Identifications of chemical compounds were made by matching their mass spectra and Kovat's indices (IK) values with known compounds reported in the literature. An Applied Separations-apparatus (Speed SFE, model 7071, Allentown, PA, EUA) was used for SFE extractions. They were conducted at pressure 200 bar and temperature 30°C (20 min in static mode and 40 min in dynamic mode). The supercritical CO2 flow rate was (6.8±0.7)×10-5 kg-CO2/s. The essential oil collected was immersed in ethylene glycol bath (5°C). The yield of essential oils obtained by SFE was larger than hydrodistillation in both fertilization treatments (279 and 333% for organic and mineral fertilizations, respectively). There were no differences between the fertilization treatments. The amount of the volatile components showed by GC-MS chromatogram was highest in the essential oil obtained by hydrodistillation than SFE. The main volatile constituents of the essential oils were trans-anethole (Hydrodistillation: organic - 52.4%; mineral - 55.0%/ SFE: Hydrodistillation - 62.8%; mineral - 66.8%) and methyl-chavicol (Hydrodistillation: organic - 37.3%; mineral - 38.3%/ SFE: organic - 8.4%; mineral - 4.3%). A reduction of methyl-chavicol relative proportion of essential oil obtained by SFE was observed. Cys-anethole, α-copaene, trans-cariofilene, germacrene-D, β-selinene, biciclogermacrene and spathulenol were expressed only in hydrodistillation. The extraction of essential oil by SFE presented larger yield of essential oil than hydrodistillation technique, presenting, however, these essential oils, different phytochemical profiles.
Keywords: Methyl-chavicol; Mineral treatment; Organic treatment; SFE; Trans-anethole; Ocimum; Ocimum selloi